Book Review of "AI Superpowers: China, Silicon Valley, and the New World Order" by Kai-Fu Lee - Alina Shymanska (International Journal of Nuclear Security, 2019)
Dr. Kai-Fu Lee’s book, AI Superpowers: China, Silicon Valley, and the New World Order, can be characterized as a glimpse of how humankind could coexist with artificial intelligence, that would render many people unemployed. The book also hints at the AI power game between the United States and China. The author claims China will be the victor due to a deeper understanding of how to implement AI technologies, as opposed to simply developing them. "I believe that the skillful application of AI will be China's greatest opportunity to catch-up - and probably surpass - the United States. But more importantly, this shift will create an opportunity for all people to discover what it is that makes us human." Dr. Kai-Fu Lee Do we live in the age of great discoveries or the age of implementation? According to Dr. Lee, the founder and president of Sinovation Ventures Artificial Intelligence Institute, the opportunities of AI such as driving a car, diagnosing diseases, and the ability to do spoken translation between different languages, "do not signify rapid progress toward 'general AI' any other similar breakthrough on a level of deep learning." Rather these constitute an implementation, just like applying electricity to lightning, the dwelling, and powering the industry.